Assessing DevOps Adoption in Saudi Software Teams - Alfawzan , Layla; Alenezi, Mamdouh; Akour, Mohammed (Journal of Posthumanism, 2025)
The global adoption of DevOps principles has transformed software development through enhanced collabo- ration, automation, and continuous improvement. However, empirical research on DevOps adoption in the Middle East, particularly Saudi Arabia, is limited. This study examines the understanding and implementation of DevOps practices among software development teams in Saudi Arabia, highlighting challenges faced. A survey of 308 team members assesses their knowledge, comprehension, and application of DevOps methodologies. Results indicate that while many respondents grasp core DevOps concepts, adoption is hindered by barriers such as inadequate knowledge, resistance to change, and insufficient training. Approximately (50)% of organizations have adopted DevOps practices, yet many participants are uncertain about their organization’s status, indicating a need for better communication and awareness. The study identifies benefits like faster software delivery and improved collaboration but emphasizes the necessity for expertise development and cultural shifts. Findings suggest that to enhance DevOps adoption in Saudi Arabia, focused efforts in training, change management, and leadership engagement are crucial. This research offers insights for policymakers, industry leaders, and software teams to boost competitiveness and efficiency in the region, with future studies recommended exploring the long-term impacts of DevOps on business performance and strategies to address identified challenges.